2018
DOI: 10.18494/sam.2018.2070
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent High-performance Dynamic Control for Two-stage Screw High-temperature Heat Pump System

Abstract: In this study, we developed a new type of water-to-water two-stage screw heat pump with a vapor injection flash tank and investigated the performance of the heat pump under various condensation temperatures of the refrigeration cycle. In addition to the flash tank, a floodedtype evaporator and a shell-tube oil cooler for refrigeration oil heat recovery are implemented in the heat pump system. Suitable vapor injection pressures corresponding to different condensation temperatures were found. It was also found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They theoretically showed that increasing the vapor injection pressure increases the amount of vapor injection and the subcooling degree of the refrigeration cycle and enhances the performance of the system. Luo and coworkers (19,20) developed an intelligent strategy for controlling the subcooling degree by sensing the condensation temperature and subcooled refrigerant temperature at the inlet of the expansion valve to dynamically obtain high performance of a heat pump at different condensation temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…They theoretically showed that increasing the vapor injection pressure increases the amount of vapor injection and the subcooling degree of the refrigeration cycle and enhances the performance of the system. Luo and coworkers (19,20) developed an intelligent strategy for controlling the subcooling degree by sensing the condensation temperature and subcooled refrigerant temperature at the inlet of the expansion valve to dynamically obtain high performance of a heat pump at different condensation temperatures.…”
Section: Introductionmentioning
confidence: 99%